Effect of Multicomponent Exercise and Nutrition Support on the Cognitive Function of Older Adults: A Randomized Controlled Trial - Imaoka M (Dove Medical Press, 2019)
Masakazu Imaoka,1–4 Hidetoshi Nakao,1,2 Misa Nakamura,1,2 Fumie Tazaki,1,2 Motohiro Maebuchi,5 Masahisa Ibuki,5 Masatoshi Takeda1,2 1Department of Rehabilitation, Osaka Kawasaki Rehabilitation University, Kaizuka, Osaka 597-0104, Japan; 2Cognitive Reserve Research Center, Kaizuka, Osaka 597-0104, Japan; 3Graduate School, Department of Comprehensive Rehabilitation, Osaka Prefecture University, Habikino, Osaka 583-8555, Japan; 4Department of Preventive Gerontology, National Center for Geriatrics and Gerontology, Obu, Aichi 474-8511, Japan; 5Planning Department, R&D Division, Fuji Oil Co., Ltd., Izumisano, Osaka 598-8540, JapanCorrespondence: Masakazu ImaokaDepartment of Rehabilitation, Osaka Kawasaki Rehabilitation University, 158 Mizuma, Kaizuka, Osaka 597-0104, JapanTel/Fax +81-72-446-6700Email imaokamasakazu@gmail.comPurpose: This study compared the effects of a combination of soy peptide supplementation and exercise with those of exercise only, on the cognitive function of elderly adults.Patients and methods: This randomized, non-blinded, controlled clinical trial included 67 participants aged 60 years or more with non-cognitive dysfunction who were divided into two groups according to the intervention method: an exercise group (Ex group, n = 36) and an exercise plus nutrition group (Ex+Nt group, n = 31). The Ex group completed a memory training activity for 15 mins and aerobic exercise for 45 mins once a week for 90 days. The Ex+Nt group completed the same training plus received soy peptide for 90 days. The Mini-Mental Status Examination score, trail-making test A/B score, skeletal muscle mass index, grip strength, gait speed, and geriatric depression scale were measured at baseline and post intervention. For comparison between the pretest and posttest measurements to determine the intervention effects, a two-way analysis of variance was performed. The significance level was set at < 5%.Results: A two-way analysis of variance revealed significant time effects on trail-making test-A score, skeletal muscle index, grip strength, and gait speed in both groups. There were significant time x group interactions for greater increase in calculation score.Conclusion: A combination of exercise and soy peptide supplementation was effective in improving a portion of cognitive function.Keywords: dementia, Alzheimer’s disease, Mini-Mental Status Examination, soy peptide